Identification of a Diverse Core Set Panel of Rice From the East Coast Region of India Using SNP Markers - Choudhury, Debjani Roy; Kumar, Ramesh; S, Vimala Devi; Singh, Kuldeep; Singh, N. K.; Singh, Rakesh (Frontiers in Genetics, 2021)
In India, rice (Oryza sativa L.) is cultivated under variety of climatic conditions. Due to the fragility of the coastal ecosystem rice farming in these areas has lagged behind. Salinity coupled with floods has added to this trend. Hence to prevent genetic erosion, conserving and characterizing the coastal rice, is the need of the hour. This work accessed the genetic variation and population structure among 2242 rice accessions originating from India’s east coast comprising of Andhra Pradesh, Orissa and Tamil Nadu, using 36 SNP markers and have generated a core set (247 accessions) as well as a mini-core set (30 accessions) of rice germplasm. All the 36 SNP loci were bi-allelic and 72 alleles found with average two alleles per locus. The genetic relatedness of the total collection was inferred using un-rooted Neighbor-joining tree, which grouped all the genotypes (2242) into three major clusters. Two groups were obtained with core set and three groups obtained with mini core set. Mean PIC value of total collection was 0.24 and that of the core collection and mini core collection were 0.27 and 0.32 respectively. The mean heterozygosity and gene diversity of the overall collection were 0.07 and 0.29 respectively and the core set and mini core sets revealed 0.12 and 0.34, 0.20 and 0.40 values respectively, representing 99% of distinctiveness in the core and mini core sets. Population structure analysis showed maximum population at K=4 for total collection and core collection. Accessions were distributed according to their population structure confirmed by PCoA and AMOVA analysis. The identified small and diverse core set panel will be useful in allele mining for biotic and abiotic traits and managing genetic diversity of the coastal rice collection. Validation of the 36 plex SNP assay was done by comparing the genetic diversity parameters across two different rice core collections i.e. east coast and northeast rice collection. The same set of SNP markers were found very effective in deciphering diversity at different genetic parameters in both the collections hence, these marker set can be utilized for core development and diversity analysis studies.